Seagrass Cymodocea nodosa across biogeographical regions and times: Differences in abundance, meadow structure and sexual reproduction. (December 2020) - Máñez-Crespo, Julia; Tuya, Fernando; Fernández-Torquemada, Yolanda; Royo, Laura; Pilar-Ruso, Yoana del; Espino, Fernando; Manent, Pablo; Antich, Laura; Castejón-Silvo, Inés; Curbelo, L.; de la Ossa, José A.; Hernan, Gema; et al.
Abstract: Seagrasses are key habitat-forming species of coastal areas. While previous research has demonstrated considerable small-scale variation in seagrass abundance and structure, studies teasing apart local from large-scale variation are scarce. We determined how different biogeographic scenarios, under varying environmental and genetic variation, explained variation in the abundance and structure (morphology and biomass allocation), epiphytes and sexual reproduction intensity of the seagrass Cymodocea nodosa . Regional and local-scale variation, including their temporal variability, contributed to differentially explain variation in seagrass attributes. Structural, in particular morphological, attributes of the seagrass leaf canopy, most evidenced regional seasonal variation. Allocation to belowground tissues was, however, mainly driven by local-scale variation. High seed densities were observed in meadows of large genetic diversity, indicative of sexual success, which likely resulted from the different evolutionary histories undergone by the seagrass at each region. Our results highlight that phenotypic plasticity to local and regional environments need to be considered to better manage and preserve seagrass meadows. Highlights: Seagrasses are key habitat-forming species worldwide. Different biogeographic scenarios explain variation in seagrass structure. Attributes of seagrass leaf canopy evidenced regional seasonal variation. Belowground allocation was driven by local-scale variation. High seed densities occurred in meadows of high genetic diversity.